Green Synthesized Zinc Oxide Nanoparticles Using Musa acuminata Corm Extract and Its Anti-Cancer Activity - Rym, Hassani (Indian Journal of Pharmaceutical Education and Research)
Background Information: Osteosarcoma is the most common type of bone cancer, typically affecting children and young adults. It primarily develops in the long bones of the arms and legs. The banana (Musa spp) is widely popular in tropical regions around the world. One of its species, the Cavendish banana (Musa acuminata), is a wild plant that thrives in tropical and subtropical climates. In recent years, the health benefits of M. acuminata have gained considerable attention. Different parts of the plant have been used in traditional medicine to treat various ailments. While some parts of M. acuminata have demonstrated anti-cancer properties, the corm has not been extensively studied. Objectives: This study investigates the anti-cancer effects of biosynthesized Musa acuminata corm extract-coated zinc oxide nanoparticles on the Saos2 osteosarcoma cell line. Materials and Methods: Zinc oxide nanoparticles coated with Musa acuminata corm extract were described in the present study using SEM, FTIR, DLS, and UV-vis to assess their characteristics. The cytotoxicity and cell proliferation of ZnO NPs and chemically synthesised ZnONPs at different doses were verified using MTT and trypan blue. Phase contrast microscopy and DAPI staining were used to examine the morphological assessment of Saos2 cells and apoptosis, respectively. Using rhodamine 123 staining and fluorescence microscopy, the membrane integrity of mitochondria was examined. Lipid peroxidation, glutathione, and nitric oxide levels were used to assess ZnO NPs' antioxidant capacity. Results: Nanoparticles characterization reveals the synthesis of Musa acuminata corm extract coated zinc oxide nanoparticles and moreover XRD patterns reveals the hexagonal shape with an average size of 75.50 and 46.42 nm respectively. The MTT assay showed significant suppression of Saos2 cells, with an IC50 of 300 μg/mL indicating 49.36% inhibition. The trypan blue exclusion assay exhibited a progressive decline in the percentage of viable cells, and phase contrast microscopy revealed morphological distortions in the treated cells. The presence of apoptotic cells was observed in DAPI staining and ROS staining. Oxidative stress biomarkers including NO and LPO were significantly increased whereas, antioxidant biomarker such as GSH decreased in the treated groups. Conclusion: Based on the research outlined above, the anticancer properties of ZnO NPs coated with Musa acuminata corm extract effectively targeted osteosarcoma cells.
Keywords: Musa acuminata; Reactive oxygen species; Wound healing; Osteosarcoma; Zinc oxide nanoparticle.